Dual-Source Procurement and Supplier Pricing Decision under Supply Interruption. (16th June 2021) - Che, Cheng; Zhang, Xiaoguang; Chen, Yi; Zhao, Liangyan; Guo, Peng; Liang, Yuqing
Abstract : The occurrence of major public health events usually leads to interruptions in the supply chain. This article studies the supply chain consisting of two suppliers and one manufacturer. In the case of supply interruptions, the manufacturer adopts two models of unit cost subsidies and proportional subsidies. The reliability of the supplier's supply is incentivized and ensured. A Stackelberg game model is established in which the manufacturer is the leader and the supplier is the follower. The research results show that the optimal order quantity of the supplier manufacturer and the optimal wholesale price of the supplier will be affected by the reliability level, and the optimal supply chain profits of the two models under different parameters are compared.